2012
DOI: 10.1007/s10439-012-0527-2
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro Characterization of Bicuspid Aortic Valve Hemodynamics Using Particle Image Velocimetry

Abstract: The congenital bicuspid aortic valve (BAV) is associated with increased leaflet calcification, ascending aortic dilatation, aortic stenosis (AS) and regurgitation (AR). Although underlying genetic factors have been primarily implicated for these complications, the altered mechanical environment of BAVs could potentially accelerate these pathologies. The objective of the current study is to characterize BAV hemodynamics in an in vitro system. Two BAV models of varying stenosis and jet eccentricity and a trileaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 39 publications
8
67
1
Order By: Relevance
“…71 They found that the smaller EOAs of bicuspid valves lead to a significant increase in fluid velocity, vorticity, TPG, and ventricular side shear stresses compared with normal tricuspid valves ( Figure 2D). However, some amount of each of these hemodynamic features seems to be critical in proper valve function.…”
Section: Hemodynamic Effects On Aortic Valve Tissuementioning
confidence: 92%
See 2 more Smart Citations
“…71 They found that the smaller EOAs of bicuspid valves lead to a significant increase in fluid velocity, vorticity, TPG, and ventricular side shear stresses compared with normal tricuspid valves ( Figure 2D). However, some amount of each of these hemodynamic features seems to be critical in proper valve function.…”
Section: Hemodynamic Effects On Aortic Valve Tissuementioning
confidence: 92%
“…For example, the normal tricuspid valve requires some amount of vorticity to facilitate rapid valve closure after systole. 71 Using a similar particle tracking and aortic valve explantation technique, Yap et al 75,76 were also able to demonstrate that the shear stresses on the ventricular side of the valve are higher than those on the aortic side. The ventricular side shear stress peaked at 64 to 71 dynes/cm 2 during systole and reversed in direction at the end of systole for only 15 to 25 milliseconds at 40 to 51 dynes/cm 2 .…”
Section: Hemodynamic Effects On Aortic Valve Tissuementioning
confidence: 98%
See 1 more Smart Citation
“…Phase-contrast magnetic resonance imaging (PC MRI) and echocardiographic measurements in BAV patients [7]- [10], as well as in vitro particle-image velocimetry measurements [11]- [13] and in silico simulations in idealized ascending aorta (AA) geometries [14]- [17] have revealed the existence of abnormal helical flow patterns and fluid wall shear stress (WSS) overloads in AA regions vulnerable to aortic medial degeneration. In addition, the particular leaflet fusion type affects the expression of dilation and thinning of the AA downstream of a BAV.…”
Section: Introductionmentioning
confidence: 99%
“…7). 17,26,[45][46][47]64,66,68,76,77,88,91,97,98,103,130,138 However, PIV methods were mainly two dimensional until Brušcker introduced Stereo-PIV based on the use of two digital cameras and PIV algorithms to study the flow past artificial heart valves. 21 The testing requirements for performing stereo-PIV for characterizing the flow through mechanical heart valves has been well described by Morbiducci et al 115 Another breakthrough in PIV was the development of defocusing digital particle image velocimetry (D-DPIV).…”
Section: Particle Image Velocimetry Of Heart Valvesmentioning
confidence: 99%